(untitled) (Research, Society and Development, 2020)
Phosphorus is the second most abundant mineral in the animal organism, and excess or deficiency can increase susceptibility to diseases of bone development. Currently, nutritionists have been looking for ways to precisely meet the phosphorus requirements of animals, as well as to know the availability of phosphorus from the ingredients used in feed, aiming at the efficient use of this mineral. Pre-cecal digestibility of phosphorus has been proposed as the closest measure to what would be available phosphorus for poultry. The methodology used was that of narrative review, with consultation of documents published in different databases in order to describe and discuss the methodologies applied to determine the pre-cecal digestibility of phosphorus in ingredients for birds. The commonly used methods are the direct method, the regression method and the substitution method. Each method has its advantages, disadvantages and limitations. In the direct method and in the substitution method, it is necessary to formulate a phosphorus-free diet for the determination of endogenous losses and subsequent correction of the apparent value to the true value. In the regression method, endogenous loss is determined by the intercept of the generated linear equation, being more costly and laborious, due to the need to formulate several diets for a single ingredient. The knowledge about the digestibility values of phosphorus in different ingredients is very important in the formulation of poultry diets, since it allows to estimate more precisely how much of the phosphorus to be used has the potential to be absorbed by the animal.